MARPE guide: A case report - Minervino, Bruno L. [UNESP]; Barriviera, Maurício; Curado, Marcelo de Morais; Gandini, Luiz G. [UNESP] (Jaypee Brothers Medical Publishing, 2019)
Aim: This paper presents a prototyped surgical guide for placement of MARPE-mini-implant-assisted rapid palatal expander. Background: Investigations conducted in the last decades have increased the technological resources used in orthodontics. This scientific advance applies to several clinical procedures, including the planning of devices used in guided surgeries, using computed tomography images and intraoral scanning. Case description: This case report presents maxillary expansion in an adult patient (18 years and 5 months), using the MARPE technique, by virtual planning and fabrication of a surgical guide (laser-printed on a 3D printer MoonRay D225-SprintRay, 2014), after merging of 3 files: digital file of the expander (. stl), computed tomography of the suture, and intraoral scanning of the patient, using the planning software NemoStudio (version 20122, 16.50.0.56). Conclusion: Fabrication of a surgical guide for the MARPE technique provides an accurate transfer of the virtual planning to the surgical procedure. It allows three-dimensional orientation of the expander position and perforations of mini-implants, which are necessary to establish anchorage in areas with sufficient bone, assuring the system stability and a successful procedure. Clinical significance: The mini-implant assisted rapid palatal expansion (MARPE) has been investigated as a promising option for correction of malocclusion related with maxillary atresia in adult patients and is an option to orthognathic surgery. Digital treatment planning is fundamental to establish individual, reproducible, and accurate parameters, as in the present case, which evidenced significant benefits in both occlusal and respiratory aspects.
Keywords: MARPE; Midpalatal suture; Rapid palatal expansion; Surgical guide